GAMBARAN PRAKTIK PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) PADA BAYI USIA 6-12 BULAN DI PUSKESMAS UMBULHARJO I KOTA YOGYAKARTA - Hayati, Efi Nur; Suesti, Suesti (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2024)
Abstract: According to the findings of the 2018 Indonesian Basic Health Research (Riskesdas), the percentage of under-fives with malnutrition and low nutrition was 13.8%, 3.9% and 19.3%, respectively, while the percentage of under-fives with short and very short height was 11.5%. The practice of giving complementary food for breastfeeding is a parenting pattern for parents in providing additional food for babies aged 6-24 months. This study aims to describe the practice of giving complementary feeding to infants aged 6-12 months at Umbulharjo I Primary Health Center in Yogyakarta. The research employed quantitative descriptive, the data collection method used was primary data and used univariate analysis. This study's findings were obtained from 32 respondents who had babies aged 6 to 12 months. A negative attitude was obtained from the mother's attitude when practicing complementary food, namely as many as 17 respondents (53.1%), and a positive attitude was obtained from the mother's actions in giving complementary food, namely as many as 22 respondents (68.8%). Thus, it can be concluded that there are still mothers with babies aged 6-12 months who have a negative attitude toward the practice of giving complementary food, but the act of giving complementary food to babies aged 6-12 months is good. As a result, Posyandu cadres and midwives at Primary Health Center must continue to counsel mothers as they prepare to give complementary food to their babies, in order to foster a positive attitude toward complementary feeding administration.Abstrak: Menurut temuan Riset Kesehatan Dasar (Riskesdas) Indonesia tahun 2018, persentase balita gizi buruk dan gizi rendah masing-masing sebesar 13,8%, 3,9%, dan 19,3%, sedangkan persentase balita dengan tinggi badan pendek dan sangat pendek adalah 11,5%. Praktik pemberian makanan pendamping ASI merupakan pola asuh orang tua dalam pemberian makanan tambahan yang ditunjukan untuk bayi usia 6 – 24 bulan. Tujuan dari penelitian ini adalah untuk mengetahui gambaran praktik pemberian makanan pendamping ASI (MP-ASI) pada bayi usia 6-12 bulan di Puskesmas Umbulharjo I Kota Yogyakarta. Rencana penelitian yang digunakan adalah deskriptif kuantitatif, metode pengumpulan data yang digunakan adalah data primer dan menggunakan analisis univariat. Hasil penelitian ini didapatkan hasil dari 32 responden ibu yang memiliki bayi usia 6-12 bulan, dari sikap ibu ketika praktik MP-ASI yang diteliti didapatkan sikap negatif yaitu sebanyak 17 responden (53,1%) dan tindakan ibu ketika praktik MP-ASI yang diteliti didapatkan tindakan baik yaitu sebanyak 22 responden (68,8%). Dengan demikian dapat disimpulkan bahwa masih terdapat ibu yang memiliki bayi usia 6-12 bulan ketika praktik pemberian MP-ASI masih memiliki sikap negatif tetapi tindakan pemberian MP-ASI yang diberikan kepada bayi usia 6-12 bulan baik. Oleh karena itu, bagi para kader posyandu maupun Bidan Puskesmas harus tetap memberikan penyuluhan bagi para ibu untuk mempersiapkan pemberian MP-ASI pada bayi nya, sehingga terciptanya sikap yang positif ketika praktik pemberian MP-ASI.